2012
DOI: 10.1073/pnas.1207028109
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the enzyme-acyl carrier protein (ACP) substrate gatekeeper complex required for biotin synthesis

Abstract: Although the pimeloyl moiety was long known to be a biotin precursor, the mechanism of assembly of this C7 α,ω-dicarboxylic acid was only recently elucidated. In Escherichia coli, pimelate is made by bypassing the strict specificity of the fatty acid synthetic pathway. BioC methylates the free carboxyl of a malonyl thioester, which replaces the usual acetyl thioester primer. This atypical primer is transformed to pimeloyl-acyl carrier protein (ACP) methyl ester by two cycles of fatty acid synthesis. The questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
128
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(139 citation statements)
references
References 24 publications
10
128
1
Order By: Relevance
“…Two enzymes from the biotin pathway, BioC (a SAM-dependent methyltransferase) and BioH (an esterase), hijack fatty acid biosynthesis by methylating malonyl-ACP, then extending it through two rounds of the fatty acid synthase cycle 17 . The crystal structure of an inactive BioH S82A mutant:pimeloyl-ACP methyl ester complex revealed the origin of the acyl-chain length specificity 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Two enzymes from the biotin pathway, BioC (a SAM-dependent methyltransferase) and BioH (an esterase), hijack fatty acid biosynthesis by methylating malonyl-ACP, then extending it through two rounds of the fatty acid synthase cycle 17 . The crystal structure of an inactive BioH S82A mutant:pimeloyl-ACP methyl ester complex revealed the origin of the acyl-chain length specificity 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we found that the generation of pimeloyl moiety in earlier steps of biotin synthesis is involved in a modified type II fatty acid biosynthetic pathway in E. coli (6)(7)(8). In the BioC-BioH pathway of pimelate synthesis, BioC methylates malonyl coenzyme A (malonyl-CoA; or ACP) and gives a methyl malonyl-thioester destined to fatty acid biosynthesis to act as a primer (6,7,9), whereas the bioH gene product demethylates the pimeloyl-ACP methyl ester to form pimeloyl-ACP after two rounds of the fatty acid elongation cycle (6,7,10). The subsequent four-step pathway functions in assembling the double rings of the biotin molecule (6-8) (Fig.…”
mentioning
confidence: 99%
“…7C), which, in combination with the inherent flexibility of the carrier arm, would allow the carrier arm to be accommodated within active sites of different structure. A paucity of carrier arm interactions with the partner enzyme active site has also been observed for phosphopantetheine-containing carrier proteins, suggesting that this strategy is a general feature of carrier protein interactions (6,(29)(30)(31).…”
Section: Discussionmentioning
confidence: 95%